ELECTROSTATIC SOLITARY WAVE STRUCTURES IN MAGNETIZED NEGATIVE ION PLASMA WITH STATIONARY DUST - Ahtar, N.; Hussain, S. (The Nucleus, 2013)
Non linear electrostatic solitary wave structures are studied in negative ion magnetized homogenous plasma in the presence of stationary dust. Zakharov-Kuznetsov (ZK) equation is derived by using reductive perturbation method. Laboratory plasma parameters are used for the numerical analysis of ZK equation. It is seen that compressive and rarefactive solitary wave structures are observed for fast and slow modes. The effects of magnetic field, obliqueness, temperature variation of positive and negative ions in the presence of dust on non linear solitary wave structures are discussed.